Comparative analysis of semaglutide induced adverse reactions: Insights from FAERS database and social media reviews with a focus on oral vs subcutaneous administration - Zhang, Jing; Wang, Xiaofen; Zhou, Yiting (Frontiers in Pharmacology, 2024)
Background: Compared to alternative weight-loss strategies and medications, semaglutide stands out for its convenience and efficacy, resulting in a significant increase in prescriptions and raising public safety concerns. Furthermore, the safety profiles of its oral and subcutaneous formulations require further examination.Objective: Our goal is to investigate the potential safety risks associated with semaglutide by analyzing data from the FAERS database and social media. Additionally, we aim to compare the adverse drug reaction (ADR) signals between the oral and subcutaneous administration routes of semaglutide. Methods ： We collected semaglutide-related reports from the FAERS database spanning Q1 2018 to Q2 2023, and patient reviews on WebMD and AskaPatient up to July 20, 2023. Following data extraction and cleansing, we conducted descriptive analyses of demographic characteristics. Subsequently, we calculated adverse drug reaction (ADR) signals using the reporting odds ratio (ROR).Results ： We identified 19,289 and 422 semaglutide-related adverse drug events (ADEs) reported in the FAERS database and online patient reviews, respectively.Gastrointestinal disorders emerged as the most commonly reported System Organ Class (SOC) in both datasets. Predominant Preferred Terms (PTs) included nausea, vomiting, and diarrhea. Serious outcomes constituted 3.07% and 2.25% of all cases for oral and subcutaneous semaglutide, respectively. At the SOC level, gastrointestinal disorders accounted for 30.19% of total ADEs in oral semaglutide, slightly surpassing the 27.76% in subcutaneous semaglutide. The median onset for gastrointestinal PTs was 4 days in both oral (Q1: 1, Q3: 32) and subcutaneous (Q1: 1, Q3: 35) formulations. Noteworthy, new serious adverse event (AE) signals were identified, including hemorrhagic diarrhea (ROR: 3.69), hepatic pain (ROR: 4.20), abnormal hormone levels (ROR: 6.51), and pancreatic failure (ROR: 36.34) in subcutaneous semaglutide, and Dupuytren's contracture (ROR: 46.85) in oral semaglutide.Conclusions：Our study delineates the safety profile of semaglutide using data from the FAERS database and social media. And identified novel ADR signals specific to oral and subcutaneous forms of semaglutide.